Pathfinders : the journeys of 16 extraordinary Black souls - Bolden, Tonya (Abrams Books for Young Readers, 2017)
Profiles sixteen high-achieving African Americans, including magician Richard Potter, concert singer Sissieretta Jones, and architect Paul R. Williams.